Diagnostic Accuracy of Serum Albumin for Diagnosis of Esophageal Varices among Patients of Chronic Liver Disease taking Endoscopy as Gold Standard - Shaista Zeb, Wafa Haider, Mohsin Shafee Rajput, Imran Arshad, Ghulam Fareed Memon, Shakir Hussain Keerio, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To determine the diagnostic accuracy of serum albumin for the detection of esophageal varices (EV) in cases presented with chronic liver disease taking Esophagogastroduodenoscopy (EGDs) as the gold standard. Methodology: This cross-sectional study was conducted at the Department of Medicine, Sir Ganga Ram Hospital, Lahore in collaboration of Department of Gastroenterology, Services Hospital, Lahore, during a period of six months. After receiving informed consent, each patient's blood was drawn using a 5cc disposable syringe and sent to the hospital's laboratory for analysis of serum albumin levels. Esophageal varices were suspected as positive on albumin level <3.5mg. Then, patients were referred to and underwent EGD. All EGDs were done on every patient by a consultant gastroenterologist having a minimum experience of 5 years. Self-made study proforma was used for the data collection and SPSS version 26 was used for the data analysis. Results: The patient’s average age was 55.44+12.51 years. Males were found in majority 70.53%. Esophageal varices were noted positive among 41.1% of the cases out of a total 95 study subjects. The sensitivity and specificity of the serum albumin in the diagnosis of esophageal varices were found to be 80.55 percent and 83.05 percent, respectively, followed by a positive predictive value 74.35 percent, negative predictive value 87.5 percent, and the diagnostic accuracy was 82.10 percent by taking EGD as the gold standard. Conclusion: Decreased serum albumin level was observed to be the non-invasive, useful predictor and as a good first-line diagnostic tool of esophageal varices among cases having chronic liver disease in clinical practice.